A divergent approach for asymmetric syntheses of (+)-spicigerine, (+)-cassine and their 3-epimers. Issue 6 (11th February 2016) - Han, Pan; Si, Chang-Mei; Mao, Zhuo-Ya; Li, Hai-Tong; Wei, Bang-Guo; Du, Zhen-Ting
Abstract: An efficient approach for asymmetric synthesis of (+)-spicigerine, (+)-cassine and their 3-epimers has been developed through the intramolecular diastereoselective tandem addition/cyclisation process of α-chiral aldimine9 with methylmagnesium bromide and the asymmetric addition of nucleophilic reagents to aminal14. Moreover, the first asymmetric synthesis of (+)-spicigerine has been achieved in this manuscript. In this synthetic strategy, the asymmetric syntheses of (+)-spicigerine and (+)-cassine was achieved in a 14% overall yield and nine steps and an 18% overall yield and seven steps from cheap α-chiral aldimine9, respectively. Graphical abstract: